1991
DOI: 10.1172/jci115061
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic dysfunction in hypertrophic cardiomyopathy. Effect on active force generation during systole.

Abstract: We tested the hypothesis that intracellular Ca++ ([Ca+Jli)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
1
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(75 citation statements)
references
References 38 publications
4
69
1
1
Order By: Relevance
“…21,22 In addition, several studies of myocardial samples from HCM patients after myectomy have suggested that functional abnormalities in Ca 2ϩ -handling proteins, including SERCA2, might be involved in abnormal intracellular Ca 2ϩ handling and thus, in impaired contractile performance in HCM patients. [23][24][25] SERCA2 is clearly recognized as a major determinant of myocardial contractility. 26 In a recent study in genetically engineered mice models, Kadambi et al 22 implicated the ratio of SERCA2 to phospholamban as a contributing factor in determining the frequency response of cardiac muscle.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 In addition, several studies of myocardial samples from HCM patients after myectomy have suggested that functional abnormalities in Ca 2ϩ -handling proteins, including SERCA2, might be involved in abnormal intracellular Ca 2ϩ handling and thus, in impaired contractile performance in HCM patients. [23][24][25] SERCA2 is clearly recognized as a major determinant of myocardial contractility. 26 In a recent study in genetically engineered mice models, Kadambi et al 22 implicated the ratio of SERCA2 to phospholamban as a contributing factor in determining the frequency response of cardiac muscle.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in the intracellular Ca 2+ concentration of myocytes may result in 2 beneficial effects on HCM. One is a decrease in contractility, which may be related to the reduction in LVPG, and the other may be closely related to the improvement in the LV diastolic dysfunction in patients with HCM, as indicated by Gwathmey et al 16 This improvement in LV diastolic dysfunction commonly observed in HCM may be caused by a decrease in the LV diastolic pressures.…”
Section: Mechanism Of the Decrease In LV Diastolic Pressures Associatmentioning
confidence: 88%
“…Gwathmey et al reported that an increase in the intracellular Ca 2+ concentration of myocytes might be related to LV diastolic dysfunction in patients with HCM. 16 Cibenzoline is known to have a weak calcium-channel blocking action 17 and a strong sodium-channel blocking action, the latter action of cibenzoline seeming to result in a marked decrease in the intracellular Ca 2+ concentration of myocytes through the Na + /Ca 2+ exchange pump. A decrease in the intracellular Ca 2+ concentration of myocytes may result in 2 beneficial effects on HCM.…”
Section: Mechanism Of the Decrease In LV Diastolic Pressures Associatmentioning
confidence: 99%
“…In contrast, SERCA2a expression is unchanged in volume-overload-induced LV hypertrophy [23]. Data on SERCA2a gene expression in the noninfarcted LV following MI are less abundant and tend to conflict, with reports of unchanged [24,25], decreased [5,7,[9][10][11]26,27] or even increased expression [28,29]. This could be due to certain particularities of this model of chronic LV hemodynamic overload.…”
Section: Introductionmentioning
confidence: 86%